2010
DOI: 10.4103/0253-7176.78504
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuro-Imaging and Post-Traumatic Olfactory Impairment

Abstract: Objective:To evaluate via a research literature survey the anterior neurological significance of decreased olfactory functioning following traumatic brain injuries.Materials and Methods:A computer literature review was performed to locate all functional neuro-imaging studies on patients with post-traumatic anosmia and other olfactory deficits.Results:A convergence of findings from nine functional neuro-imaging studies indicating evidence for reduced metabolic activity at rest or relative hypo-perfusion during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Some evidences confirmed that directing attention to the prepulse stimulus could enhance PPI response (Heekeren et al, 2004 ; Annic et al, 2014 ). In patients, attentive deficit was found in anosmia cases (Roberts et al, 2010 ; Garcia-Sanchez et al, 2011 ). Olfactory sensory stimulus affected on the attentional response by top-down regulations via descending axonal projections from forebrain structures (Georgoussi et al, 1990 ; Yochman et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidences confirmed that directing attention to the prepulse stimulus could enhance PPI response (Heekeren et al, 2004 ; Annic et al, 2014 ). In patients, attentive deficit was found in anosmia cases (Roberts et al, 2010 ; Garcia-Sanchez et al, 2011 ). Olfactory sensory stimulus affected on the attentional response by top-down regulations via descending axonal projections from forebrain structures (Georgoussi et al, 1990 ; Yochman et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correia et al (2001) found that only one of a group of 15 patients with mild TBI and anosmia reported chronic unemployment problems, using the same criteria as Varney. Another study found no difference between an anosmic and a nonanosmic group of TBI patients of varying severity in employment status after injury (Crowe & Crowe, 2013). Further the review by Roberts et al (2010) concluded that there was not enough data on real world outcomes, such as vocational dysfunction, to draw conclusions about whether posttraumatic anosmia has ecological validity as an indicator of poor psychosocial prognosis.…”
Section: Hyposmiamentioning
confidence: 99%
“…This damage to the olfactory nerve is typically associated with contusions and lacerations of the surrounding orbital frontal cortical areas (Jennett & Teasdale, 1981) leading researchers to suggest that anosmia can be used as an indicator of orbitofrontal damage following brain injury (Varney, 1988). Recent research has repeatedly demonstrated this association (for a review, see Roberts, Sheehan, Thurber, & Roberts, 2010). As an indicator of orbitofrontal damage, then, it might be expected that hyposmia would be associated with socially disinhibited behavior following TBI, which likely results from damage to the same brain region.…”
Section: Hyposmiamentioning
confidence: 99%
“…The use of functional imaging such as SPECT provides information about cerebral metabolism and perfusion (4) . Previous studies have shown reliable results in diagnosing anosmia by employing SPECT (5) .…”
Section: Introductionmentioning
confidence: 98%